Plant-produced RBD and cocktail-based vaccine candidates are highly effective against SARS-CoV-2, independently of its emerging variants - Mamedov, Tarlan; Yuksel, Damla; Gurbuzaslan, Irem; Ilgin, Merve; Gulec, Burcu; Mammadova, Gulshan; Ozdarendeli, Aykut; Pavel, Shaikh Terkis Islam; Yetiskin, Hazel; Kaplan, Busra; Uygut, Muhammet Ali; Hasanova, Gulnara (Frontiers in Plant Science, 2023)
SARS-CoV-2 is a novel and highly pathogenic coronavirus, which has caused an outbreak in Wuhan City, China, in 2019 and then spread rapidly throughout the world. Although several COVID-19 vaccines are currently available for mass immunization, they are less effective against emerging SARS-CoV-2 variants, especially the Omicron (B.1.1.529). Recently, we successfully produced receptorbinding domain (RBD) variants of spike (S) protein of SARS-CoV-2 and an antigen cocktail in Nicotiana benthamiana, which are highly produced in plants and elicited high-titer antibodies with potent neutralizing activity against SARS-CoV-2. In this study, based on the neutralization ability, we demonstrate that plant produced RBD, and cocktail-based vaccine candidates are highly effective against SARS-CoV-2, independently of its emerging variants. These data support that plant produced RBD, and cocktail-based antigens are most promising vaccine candidates and may protect against Delta and Omicron-mediated COVID-19. This is the first report describing vaccines against SARS-CoV-2, which demonstrates significant activities against Delta and Omicron variant.